2020
DOI: 10.1108/jpmh-11-2019-0090
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a participatory approach to improve healthy eating and physical activity in a secure mental health setting

Abstract: Purpose The prevalence of obesity in secure mental health units is higher than in the general population, having a negative impact on the physical health and mental well-being of people with severe mental health illness (SMI). The purpose of this study was to describe the feasibility of a programme aimed to help people with SMI to eat healthily and be physically active. Design/methodology/approach A mixed-methods approach was used. A questionnaire administered to patients in both wards measured acceptability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Accommodating senior‐level staff, encouraging staff buy‐in can increase participation and improve outcomes in physical activity interventions (Mateo‐Urdiales et al, 2020). The studies included in our review reported varied levels of attendance, with group sessions the best attended.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accommodating senior‐level staff, encouraging staff buy‐in can increase participation and improve outcomes in physical activity interventions (Mateo‐Urdiales et al, 2020). The studies included in our review reported varied levels of attendance, with group sessions the best attended.…”
Section: Discussionmentioning
confidence: 99%
“…Secure settings by their isolated and restrictive nature, can influence levels of physical activity (Mateo‐Urdiales et al, 2020) and obesity (Long et al, 2014). Prescription medication, comorbid cardiometabolic and other health issues may also influence motivation or capacity to exercise (Stubbs & Rosenbaum, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, they often have little input from service users throughout their development, consequently underrepresenting the 'patient voice'. This is important as co-design is likely to increase sustainability of the intervention and improve engagement by valuing patient experience throughout development (17,31).…”
Section: Rationalementioning
confidence: 99%
“…While some of the reasons for insufficient physical activity and excessive sedentary behaviour are common across both inpatient and community settings, such as the sedative effects of psychotropic medicine [15] and mental health symptoms (lack of motivation, anhedonia, fatigue and negative body image) [13], there are some unique barriers presented by inpatient settings. For example, lack of appropriate facilities, lack of suitably trained staff to support physical activity, and restrictions on leave for people detained under mental health legislation all contribute to decreased opportunities for physical activity in inpatient settings [16][17][18][19]. However, inpatient physical activity programmes provide an opportunity to improve patients' physical and mental health.…”
Section: Introductionmentioning
confidence: 99%